2017
DOI: 10.1186/s13014-017-0875-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of hearing preservation related to tumor morphologic analysis in acoustic neuromas treated by gamma knife radiosurgery

Abstract: BackgroundGamma Knife radiosurgery (GKRS) is an important part of the neurosurgical armamentarium in the treatment of acoustic neuromas. However, the treatment outcome related to the morphology of the tumor has not been rigorously studied. In this cohort, we evaluated the morphological features of the tumor in the tumor response and neurological outcomes after GKRS.Material and methodsFrom July 2003 to December 2008, there were 93 cases of acoustic neuromas treated upfront with GKRS with 64 cases with servicea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
13
0
1
Order By: Relevance
“…If patients experienced new neurological deficits (increased seizure frequency, impairment sensory of motor function), they underwent additional imaging examinations at the time of newly neurological deficits to evaluate for radiologic changes associated with these clinical changes. The assessment of volume alteration was based on our previous investigation with volume enlargement by 20% defined as increase, volume reduction by 20% defined as decrease, and volume changes of less than 20% from baseline defined as stable [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…If patients experienced new neurological deficits (increased seizure frequency, impairment sensory of motor function), they underwent additional imaging examinations at the time of newly neurological deficits to evaluate for radiologic changes associated with these clinical changes. The assessment of volume alteration was based on our previous investigation with volume enlargement by 20% defined as increase, volume reduction by 20% defined as decrease, and volume changes of less than 20% from baseline defined as stable [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three studies did not specify the cochlear dose parameter but instead referred to it simply as "cochlear dose". 29,34,35 Only a point dose at the modiolus was calculated in one study. 13 While most studies stated that volumetric cochlear dosimetry was performed, whether the maximum cochlear dose corresponded to a point or volume maximum was not always stated.…”
Section: Cochlea Contouring and Dosimetrymentioning
confidence: 99%
“…8 While Pan and colleagues reported that 81.2% of patients maintained serviceable hearing with a dose of 12 Gy prescribed to the 50% isodose line, they found that cochlear and brainstem doses did not predict hearing outcomes. 33…”
Section: Effect Of Radiation Dosementioning
confidence: 99%